Stressful events, social health issues and psychological distress in Aboriginal women having a baby in South Australia: implications for antenatal care. Issue 1 (December 2016) - Weetra, Donna; Glover, Karen; Buckskin, Mary; Kit, Jackie; Leane, Cathy; Mitchell, Amanda; Stuart-Butler, Deanna; Turner, May; Yelland, Jane; Gartland, Deirdre; Brown, Stephanie
Abstract Background Around 6 % of births in Australia are to Aboriginal and Torres Strait Islander families. Aboriginal and Torres Strait Islander women are 2–3 times more likely to experience adverse maternal and perinatal outcomes than non-Aboriginal women in Australia. Methods Population-based study of mothers of Aboriginal babies born in South Australia, July 2011 to June 2013. Mothers completed a structured questionnaire at a mean of 7 months postpartum. The questionnaire included measures of stressful events and social health issues during pregnancy and maternal psychological distress assessed using the Kessler-5 scale. Results Three hundred forty-four women took part in the study, with a mean age of 25 years (range 15–43). Over half (56.1 %) experienced three or more social health issues during pregnancy; one in four (27 %) experienced 5–12 issues. The six most commonly reported issues were: being upset by family arguments (55 %), housing problems (43 %), family member/friend passing away (41 %), being scared by others people's behavior (31 %), being pestered for money (31 %) and having to leave home because of family arguments (27 %). More than a third of women reporting three or more social health issues in pregnancy experienced high/very high postpartum psychological distress (35.6 % versus 11.1 % of women reporting no issues in pregnancy, Adjusted Odds Ratio = 5.4, 95 % confidence interval 1.9–14.9). Conclusions The findings highlight unacceptably high rates of social health issues affecting Aboriginal women and families during pregnancy and high levels of associated postpartum psychological distress. In order to improve Aboriginal maternal and child health outcomes, there is an urgent need to combine high quality clinical care with a public health approach that gives priority to addressing modifiable social risk factors for poor health outcomes.